Ultrafast valence to non-valence excited state dynamics in a common anionic chromophore - James N. Bull (Nature Portfolio, 2019)
Photoactive biomolecules rely on chromophores whose photochemistry depends on the environment. Here, the excited state dynamics of a model for the anionic biochromophore in photoactive yellow protein is investigated by time-resolved photoelectron spectroscopy showing involvement of a non-valence state, and lack of E-Z isomerisation in the gas phase.